Cell-Based Strain Remodeling of a Nonfibrous Matrix as an Organizing Principle for Vasculogenesis - Daniel Rüdiger; Kerstin Kick; Andriy Goychuk; Angelika M. Vollmar; Erwin Frey; Stefan Zahler (Cell Reports, 2020)
Summary: Endothelial tube formation on a reconstituted basement membrane (Matrigel) is a well-established in vitro model for studying the processes of angiogenesis and vasculogenesis. However, to date, the organizing principles that underlie the morphogenesis of this network and that shape the initial process of cells’ finding one another remain elusive. Here, we identify a mechanism that allows cells to form networks by mechanically reorganizing and stiffening their extracellular matrix, independent of chemical guidance cues. Interestingly, we find that this cellular self-organization strongly depends on the connectivity, plasticity, and topology of the surrounding matrix; cell contractility; and cell density. Cells rearrange the matrix and form bridges of matrix material that are stiffer than their surroundings, thus creating a durotactic track for the initiation of cell protrusions and cell-cell contacts. This contractility-based communication via strain stiffening and matrix rearrangement might be a general organizing principle during tissue development or regeneration.